Categorization by Score of Mosquito Species (Diptera: Culicidae) Related to Yellow Fever Epizootics in Argentina. Issue 5 (12th July 2022) - Cano, Maria Eugenia; Marti, Gerardo Anibal; Alencar, Jeronimo; Silva, Shayenne Olsson Freitas; Micieli, Maria Victoria
Abstract: The mosquito-borne yellow fever virus (YFV) is the cause of a zoonotic disease, with both sylvatic and urban cycles. Some mosquito species have been associated directly with transmission of the virus in South America, although the importance given to each species varies depending on the bibliography, geographical location, or year of publication. For Argentina, few publications have assessed the involvement of mosquito species, especially those included in the sylvatic cycle. Therefore, the goal of our paper was to gather all the information available in South America and categorize all mosquito species potentially involved in the YFV transmission cycle in Argentina according to incriminating vector criteria. Based on three main characteristics ('Hosts', 'Mosquito vector', and 'YF outbreak'), we generated scales of importance by species, one exclusively for Argentina and another for all of South America, Sabethes albiprivus Theobald, 1903 was the most important species in Argentina; whereas the most important species in South America were Haemagogus janthinomys Dyar 1921, Hg. leucocelaenus Dyar and Shannon, 1924, and Sa. chloropterus Von Humboldt, 1819. Our review highlights the lack of research that evaluates the importance of these species for YFV transmission in Argentina, while serving as a starting point to establish priorities for research on the bionomics and vector status of these species.